Hypokalemic periodic paralysis in subclinical hyperthyroidism: A case report - Eunike Vania Christabel; Onggo Williyanto (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Hypokalemia is a common electrolyte abnormality often encountered in daily practice. While mild hypokalemia often asymptomatic, moderate-to-severe hypokalemia usually manifested as significant symptoms such as muscle weakness. In this paper, we presented a case of 23-years-old male coming to our emergency department because of muscle weakness in all his four limbs when he woke up in the morning. Physical examinations were all within normal limit, except that his muscle strength decreased in all four extremities. Laboratory measures showed severe hypokalemia (1.9 mmol/L), hence patient was treated with potassium infusions. During hospitalization, thyroid function tests revealed hyperthyroidism. Therefore, in patient with paralysis, in which laboratory finding showed hypokalemia, hyperthyroidism should be considered as one of the potential diagnosis especially in younger patient, even in patient without previous history of hyperthyroidism. Merely treating hypokalemia in patient with underlying hyperthyroidism could be a dangerous boomerang.